Oreocharis crispata, a new species of Oreocharis (Gesneriaceae) from Guangxi, China - Chen, Run-Zheng; Chen, Wen-Hong; Wei, Yi-Gang; Wen, Fang; Yu, Xun-Lin; Shui, Yu-Min (Phytotaxa, 2017)
Oreocharis crispata, a new species of Oreocharis (Gesneriaceae) from northeastern Guangxi, China, is described and illustrated. The new species is compared with its most morphologically similar species O. nemoralis and O. magnidens. Besides, the relationship between the new species and Oreocharis × heterandra is discussed here.